2019
DOI: 10.1155/2019/9651369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality on Shape-Based Design Activities

Abstract: As the literature demonstrates, designers’ personality influences design activities like different ways to represent environments and/or products, technological advances, etc.. Nevertheless, an exhaustive analysis on the influence of personality on design activities involving different representations is missing. This research explores this gap by studying this influence on specific design activities, the shape-based ones (i.e., analysis of specific shapes and highlighting of functions suggested by them). Peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Four metrics have been selected from the literature to use in the framework. They are quantity, usefulness, novelty, and variety, as described in the research reported in [23,24]. The selection of these metrics makes it easier to explore possible relationships between personality traits and ChatGPT use, since previous research has established a relationship between the big five personality traits [25,26] and design activities.…”
Section: Highlighting the Metricsmentioning
confidence: 99%
“…Four metrics have been selected from the literature to use in the framework. They are quantity, usefulness, novelty, and variety, as described in the research reported in [23,24]. The selection of these metrics makes it easier to explore possible relationships between personality traits and ChatGPT use, since previous research has established a relationship between the big five personality traits [25,26] and design activities.…”
Section: Highlighting the Metricsmentioning
confidence: 99%
“…Regarding the internal variables (skill, knowledge, and personality), there is much literature about the definition of skill and knowledge and about their influences on design [16][17][18][19][20]. Personality deserves more attention because this research refers directly to its components, the traits.…”
Section: Possible Influences On Performancementioning
confidence: 99%